Scenarios for Dealing with the Nursing Services Tariff Setting Act Based on the Policy Analysis Triangle Model - Kamran Bagheri Lankarani; Hamid Izadbakhsh; Saeed Nojaba; Mohammad Azadi Ahmadabadi; Mohammad Saeed Saffari (مجله علوم پزشکی صدرا, 2021)
Introduction: The Nursing Services Tariff Setting and Adjustment of Nursing Fees Act and Productivity Improvement Act for Clinical Staff have not been adequately implemented after more than ten years of approval. However, various pressures that put the health system in a difficult situation should be considered carefully. This study aims to make a multilateral analysis of nursing services tariff setting, its policy, and executive dimensions. Scenarios confronting the nursing services tariff setting are explained and evaluated. Methods: The study followed a qualitative approach using library studies. The authors selected the participants using purposive sampling, while they collected data through semi-structured and in-depth interviews. Library data were analyzed and implicated using the stakeholder analysis method. The "policy analysis triangle" model has also been used to take a comprehensive and coherent approach to data collection, analysis, and presentation. Results: The research findings were categorized into four dimensions of this model, namely policy content, context, process, and actors, which clarified the required scientific and theoretical foundations, the existing documents in the field of pricing, the history and components of pricing, and the views of the main stakeholders on this issue. Conclusion: In conclusion, possible scenarios have been evaluated to ensure both nurses' satisfaction and motivation while maintaining the quality of health services. Also, some suggestions have been made for short-term and medium-term actions that can provide the opportunity for fundamental reforms by reducing the current crisis severity.